The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s10194-016-0633-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of non-invasive vagus nerve stimulation for the treatment of chronic cluster headache

Abstract: BackgroundCluster headache (CH) is a debilitating condition that is generally associated with substantial health care costs. Few therapies are approved for abortive or prophylactic treatment. Results from the prospective, randomised, open-label PREVA study suggested that adjunctive treatment with a novel non-invasive vagus nerve stimulation (nVNS) device led to decreased attack frequency and abortive medication use in patients with chronic CH (cCH). Herein, we evaluate whether nVNS is cost-effective compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…Vagus nerve stimulation has been considered to be a valuable therapeutic option for neurologic diseases, but its use has been limited by the need for invasive surgical procedures ( 28 ). The viability of non-invasive methods for stimulating the vagus nerve using portable devices that are more practical, convenient, and cost effective (versus iVNS) has expanded the therapeutic potential of VNS for a larger patient population and improved its accessibility for use in further studies ( 28 , 29 ). In our study, we observed that further increases in stimulation intensity beyond 15 V only slightly increased the responder rate and produced only a slight increase in the size of the response ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vagus nerve stimulation has been considered to be a valuable therapeutic option for neurologic diseases, but its use has been limited by the need for invasive surgical procedures ( 28 ). The viability of non-invasive methods for stimulating the vagus nerve using portable devices that are more practical, convenient, and cost effective (versus iVNS) has expanded the therapeutic potential of VNS for a larger patient population and improved its accessibility for use in further studies ( 28 , 29 ). In our study, we observed that further increases in stimulation intensity beyond 15 V only slightly increased the responder rate and produced only a slight increase in the size of the response ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A US analysis calculated annual cost related to Botox treatment of 4902 US $, which is higher compared to both the individual funding request setting as well as the time-based average cost setting (Rothrock 2011 ). A German economic analysis of chronic cluster headache treatment assessed a comparable cost decrement of €414 for a non-invasive neuromodulatory technique in addition to standard of care (Morris et al 2016 ). .…”
Section: Discussionmentioning
confidence: 99%
“…The VNS treatment was superior to sham in ECH but not in CCH [109]. Regarding the economic aspect, the cost-effectiveness of the non-invasive VNS (the gammaCore® device) for the acute treatment of both ECH and CCH was superior to the standard of care [110,111].…”
Section: Cluster Headachementioning
confidence: 99%